Helmet for my pillow - Leckie, Robert, 1920-2001. (New York : Random House, 1957)
Leckie provides one of the most riveting first-person accounts ever to come out of WWII. Follow his odyssey, from basic training to the raging battles in the Pacific.
Keywords: Leckie, Robert, -- 1920-2001.; Leckie, Robert, -- 1920-2001.; 1939-1945; World War, 1939-1945 -- Personal narratives; Personal narratives